2019
DOI: 10.1002/rra.3545
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variation in spawning success of striped bass (Morone saxatilis) in the Saint John River, New Brunswick

Abstract: Barriers such as dams have been cited as a serious threat to striped bass survival, especially when they affect or impede migration and access to spawning grounds. On the Saint John River, New Brunswick, the installation of the large Mactaquac Dam in the immediate vicinity of a historic striped bass spawning location was suspected to have caused the arrest of striped bass reproduction and the collapse of the native striped bass population. In 2014, juvenile striped bass of confirmed Saint John River origin wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…Multistate emergency management measures implemented by the ASMFC in the United States resulted in the recovery of most US populations during the 1990s and 2000s (ASMFC, 2019; Richards & Rago, 1999), although abundance estimates have since declined in the 2010s (ASMFC, 2019). In Canada, the closure of commercial fisheries and restrictions on recreational fishing led to the recovery of some populations (Miramichi River and Shubenacadie River) and not others (Saint John River, Annapolis River, and St. Lawrence River; Andrews, Linnansaari, Leblanc, Pavey, & Curry, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Multistate emergency management measures implemented by the ASMFC in the United States resulted in the recovery of most US populations during the 1990s and 2000s (ASMFC, 2019; Richards & Rago, 1999), although abundance estimates have since declined in the 2010s (ASMFC, 2019). In Canada, the closure of commercial fisheries and restrictions on recreational fishing led to the recovery of some populations (Miramichi River and Shubenacadie River) and not others (Saint John River, Annapolis River, and St. Lawrence River; Andrews, Linnansaari, Leblanc, Pavey, & Curry, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This listing was a result of the apparent loss of recruitment in 2 of the 3 known striped bass spawning rivers within the Bay of Fundy: the SJR (New Brunswick) and the Annapolis River (Nova Scotia). The Shubenacadie River in Nova Scotia currently remains as the region's sole recognized spawning location (but see Andrews et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Stock declines in the SJR attributed to unregulated commercial harvest occurring until 1978 (Andrews et al 2017) likely compounded upon the impact to spawning habitats observed in the downstream vicinity of the large Mactaquac Dam following its completion in 1968 (Bradford et al 2015, Andrews et al 2017, 2020a. Concomitantly, there has been no evidence of spawning or recruitment through infrequent searches since the mid-1970s (Dadswell 1975, DFO 2007, Andrews et al 2017.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations